The design, construction and evaluation of a test chamber for measuring rangehood capture efficiency. (2nd July 2020) - Meleika, Sammy; Hicks, Trey; Pate, Michael; Sweeney, James
Abstract : There are no ASHRAE/HVI standards for characterizing or specifying acceptable values of capture efficiency (CE) (i.e. percentage of cooking-contaminants captured/exhausted by a household rangehood). A test method, ASTM-E3087.18, was recently published describing a facility/procedure for attaining consistent CE measurements. This study presents the design, construction and operation of the first CE test-facility assembled from the ground-up following this ASTM standard. Aside from this facility, there is one other nonproprietary test-facility for standardized testing of rangehoods in accordance with ASTM-E3087.18, namely Lawrence Berkeley National Laboratory (LBNL) where a chamber was designed and built for the purpose of developing ASTM-E3087.18. Additionally, several CE tests were performed using the described test-facility to compare results with previously published data. Similar to LBNL results, 93% of CE-tests had standard deviations less than 2.0% during a test, with non-conformances attributed to inadequate steady-state times prescribed by ASTM-E3087.18 and inlet design. Using the precision/bias procedure in ASTM-E3087.18, CE-uncertainties ranged from 0.7–3.3%, with 89% of tests having 2% uncertainty or less. A preliminary repeatability analysis showed 91% of cases repeated more than once were repeatable within 10% (i.e. ±5%) and 77% of cases repeatable within 6%(i.e. ±3%). Preliminary results showed CE increasing with flowrate, though uncertainty/repeatability appear unaffected by flowrate.